Ethics Counselors as a New Priesthood - Michalos, Alex C. (Journal of business ethics, 2001)
The aim of this paper is to critically evaluate the thesis that ethics counselors constitute a new priesthood in the pejorative sense of this term. In defense of the thesis, an account is given of the diverse variety of fundamental ideas about ethics or morality. The underlying argument is simply that there is such a diversity of opinion about so many fundamental issues that most ethical appraisals, especially in committees, are probably very shallow and barely warranted. Following this negative work, an attempt is made to try to find some positive benefits from the work of ethics counselors. Some potential benefits are identified, but there is a need for empirical research in order to construct a more persuasive case for such work. In the penultimate section of the paper I addressed some of my own second thoughts about the discussion and some provocative suggestions that friends gave me about earlier drafts.